Dragonbreath: Nightmare of the Iguana #8 - Vernon, Ursula (New York, N.Y. : Dial Books for Young Readers, 2013)
Wendell the iguana's dreams are all nightmares and a Dream Wasp wants him as a host for her eggs--so, with Great-grandfather Dragonbreath's help, Danny the dragon and Suki the salamander enter Wendell's dreams to try and defeat the wasp.
Keywords: Nightmares -- Juvenile fiction; Iguanas -- Juvenile fiction; Dragons -- Juvenile fiction; Salamanders -- Juvenile fiction; Wasps -- Juvenile fiction; Best friends -- Juvenile fiction; Adventure and adventurers -- Fiction; Nightmares -- Fiction; Iguanas -- Fiction; Dragons -- Fiction; Salamanders -- Fiction; Wasps -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Adventure fiction